Digitalization of Evidence in the Constitutional Court: Opportunities and Requisite - Muhammad Fauzan; Handar Subhandi Bakhtiar (Veteran Law Review, 2023)
Digitization has spread to people's live, it is also necessary to reform the judiciary for the efficiency and effectiveness of evidence in procedural law. Legalization rather than the use of digitalized evidence is also needed for legal certainty in proceedings. The research method used in this study is a normative legal method with a historical approach and statutory approach. The historical approach is used to analyze the background of constitutional cases in the past and is connected to current conditions related to evidence. A statutory approach is needed to analyze the legality of using digital evidence when taking proceedings at the Constitutional Court. The results of this study are found that the history of constitutional cases that have relevance to the existence of the Constitutional Court is the background for the occurrence of evidence in the institution that guards the constitution. The use of digital evidence has proven necessary to realize the principle of fast, easy and cheap process. In addition, its practical use is only limited to the administrative affairs of the court clerks, not to the evidentiary process in the Procedural Law of the Constitutional Court. So that it is necessary to adapt the court to digitalization to get to the proof stage by carrying out legal formulations in the form of changes to the procedural law of the Constitutional Court which will provide space for evidence in digital form in proceedings at the Constitutional Court.